Criminal liability for an act of terrorism under the laws of the Republic of Kazakhstan: historical and legal review - Serikbayeva, S.S.; Mavlianov, А.S. (KSU publ., 2016)
The article considers the peculiarities of regulating the composition of the act of terrorism in the current laws and regulations applicable in the territory of Kazakhstan. Authors considered criminal laws of the Soviet period (The Criminal code of RSFSR of 1922, the Criminal code of RSFSR of 1926, the Criminal code of KAZSSR of 1959) and the modern Kazakhstan legislation (The Criminal code of the Republic of Kazakhstan of 1997 and the Criminal code of the Republic of Kazakhstan of 2014). Analysis of changes and amendments to the Criminal Code of the Republic of Kazakhstan includes the theoretical basis of legal innovations of recent years.
Keywords: act of terrorism; the history of criminal law; the Soviet criminal law; the law of the sovereign Kazakhstan